METODE PENAFSIRAN DR. HALO-N DALAM AL-FATHUN NAWA - Ilham Mustafa (Jurnal Pemikiran Islam, 2023)
Many methods have been developed by commentators in interpreting the Quran, resulting in diverse methods of interpreting the Quran. One of them is Dr. Halo-N, who created the concept of Quran interpretation in his book Al-Fathun Nawa. This research aims to examine the method of interpretation in the book Al-Fathun Nawa authored by Dr. Halo-N. The research uses a qualitative-descriptive method, while the type of research used is a study of figures. The results of the research show that Dr. Halo-N's method of interpretation is based on the concept of the Quran interpreting the Quran. It is a method and concept of interpreting and translating the verses of the Quran that he believes can explain the meaning of the verses and their logic without including other evidence and sources to avoid doubt. Meanwhile, the characteristic of his interpretation is scientific, as Dr. Halo-N discovered theories through correlation points he referred to as the 2D HMBC spectrum. The characteristic of Dr. Halo-N's interpretation is that the book Al-Fathun Nawa is a work that combines aspects of religion and science.